2015
DOI: 10.1515/acve-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation And Differentiation Potential Of Canine Synovial Fluid Cells

Abstract: The aim of this study was to determine whether synovial fl uid (SF) of dogs contains cells that have characteristics of MSCs and to describe their differentiation potential. SF adherent cells from 5 young German shepherd dogs (average 3.8 ± 0.9 years) were expanded (37ºC, 5% CO 2 , humidifi ed atmosphere) three weeks before their phenotype was characterized by fl ow-cytometry for the presence of CD90 and CD34. Population doubling time (PDT), number of CFU-F and adipogenic, osteogenic and chondrogenic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although SF of the osteoarthritic knee presents fewer MSC than the synovium, both have similar proliferation potential during in vitro expansion [17]. Besides, studies in equine [11, 18], canine [19], and humans [20] indicated that SF-MSC could be useful for treatment of cartilage defects and OA, as suggested in a review published by our group [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although SF of the osteoarthritic knee presents fewer MSC than the synovium, both have similar proliferation potential during in vitro expansion [17]. Besides, studies in equine [11, 18], canine [19], and humans [20] indicated that SF-MSC could be useful for treatment of cartilage defects and OA, as suggested in a review published by our group [21].…”
Section: Introductionmentioning
confidence: 99%